Impact of Train Schedule on Pedestrian Movement on Stairway at Suburban Rail Transit Station in Mumbai, India - Shah Jiten; Joshi Gaurang; Parida Purnima; Arkatkar Shriniwas (Advances in Civil Engineering)
Pedestrian flow takes place in confined environment on stairways under the influence of composition, direction of movement, and schedule of trains. During peak-period, alighting and boarding rate is quite high resulting in very high pedestrian movement from one platform to the other to catch the next train at interchange stations. The transfer of passengers from railway platforms through common undivided stairways becomes difficult, uncomfortable, and unsafe at times when pedestrian flow reaches the capacity level. Understanding of criteria defining quality of flow that affect the effectiveness of facilities like stairways in handling the pedestrian traffic is vital for planning and designing of such facilities to ensure the desired level of service as well as safety in case of emergency. The present paper is based on the study of pedestrian movement on stairways at busy suburban rail transit interchange station at Dadar in Mumbai, India. Pedestrian movements are captured through videography at two stairways and the effect of bidirectional movement on average walking speed is analyzed. The ascending flow in small proportion is found to be more influential in causing speed reduction on undivided stairways. The outcome of the study is useful for capacity and level of service analysis while planning and designing the transit station stairways.